Data from: Leading-edge vortices over swept-back wings with varying sweep geometries ... - Lambert, William B.; Stanek, Mathew J.; Gurka, Roi; Hackett, Erin E. (Dryad, 2019)
Micro air vehicles are used in a myriad of applications, such as transportation and surveying. Their performance can be improved through study of wing designs and lift generation techniques including leading-edge vortices (LEVs). Observation of natural fliers, e.g., birds and bats, has shown that LEVs are a major contributor to lift during flapping flight, and the common swift (Apus apus) has been observed to generate LEVs during gliding flight. We hypothesize that non-linear swept-back wings generate a vortex in the leading-edge region, which can augment the lift in a similar manner to linear swept-back wings (i.e., delta wing) during gliding flight. Particle image velocimetry experiments were performed in a water flume to compare flow over two wing geometries: one with a non-linear sweep (swift-like wing) and one with a linear sweep (delta wing). Experiments were performed at three spanwise planes and three angles of attack at a chord-based Reynolds number of 26,000. Streamlines, vorticity, swirling ... : Experimental DataPIV velocity measurements in .vec and .mat formats - see readme.m inside the zip file.OpenScience_Data.zip ...